3-Dimensional Modeling Training for Pre-Service Teachers Through The Tinkercad Platform - Fadhlan Muchlas Abrori; Maulana Ahsan Fadhail (Communautaire: Journal of Community Service, 2025)
The ability to develop 3D modelling is very important for educators because of its potential for further development in augmented reality and virtual reality. This paper describes the training activities for making 3D modelling for preservice teachers. The training was centred on the use of the Tinkercad platform. Pre-service teachers were asked to create 3D models of Mbaru Niang and the Grand Mosque of West Sumatra. The evaluation was conducted to assess the extent to which preservice teachers utilised the features in Tinkercad. In making Mbaru Niang, pre-service teachers generally use different forms of objects (basic objects made from cones or paraboloids), but with the same features (group, hole, and alignment). In contrast, when creating the Great Mosque of West Sumatra, pre-service teachers use the same basic object (a pyramid), but with additional features, such as a mirror. The results of this community service indicate that each teacher employs a similar approach in one 3d model project and different approaches in other projects. This study can serve as a starting point for future research or community service, providing a foundation for a similar long-term project that develops a more complex 3D model.